Systematization of scientific approaches in the contemporary motivation system and staff incentives - A. J. Bonyani (Управление)
The article is devoted to the analysis of scientific approaches to the staff motivation and incentive systems in contemporary conditions. The dynamically developing world poses ever new challenges for mankind. They can be solved only with professionally formed human capital. Therefore, the author presents in the article an analysis of the existing types and forms of personnel motivation and incentive systems, and also highlights the factors of the modern world that dictate the introduction of new tools and methods for motivating employees of enterprises. Such factors are digitalisation processes that require the acquisition of new competencies in this area not only for specialists and management personnel, but also for workers involved in the production of tangible products and the provision of services. Another equally important factor is the crises (financial, political, pandemic, military actions, etc.), which have occurred several times over the past twenty years, and under these conditions, managers and business leaders are forced to change approaches and make changes to existing employees’ motivation systems. The conducted research can be reflected in the development of systems for motivating and stimulating personnel in modern conditions.